Galangin Attenuates Isoproterenol-Induced Inflammation and Fibrosis in the Cardiac Tissue of Albino Wistar Rats - Thangaiyan, Radhiga; Arjunan, Sundaresan; Govindasamy, Kanimozhi; Khan, Haseeb A.; Alhomida, Abdullah S.; Prasad, Nagarajan Rajendra (Frontiers in Pharmacology, 2020)
Galangin (GA) is an active flavonoid of the rhizome of Alpinia galanga that belongs to the ginger family. Galangin exhibit potent anti-inflammatory properties. Therefore, we evaluated the preventive effects of GA against isoproterenol (ISO)-induced inflammation and myocardial fibrosis in male albino Wistar rats. We found that GA (1 mg/kg b.wt.) pretreatment prevented the ISO-mediated (5 mg/kg b.wt. for 14 consecutive days) elevation of activities of aspartate aminotransferase (AST), alanine aminotransferase (ALT), lactate dehydrogenase (LDH), creatine kinase (CK), creatine kinase-MB (CKMB) in the rat serum. We also noticed that GA attenuates the ISO-mediated cardiac markers i.e. cardiac troponin T and I (cTnT and cTnI) expression in the serum of rats. Further, the GA pretreatment prevented ISO-mediated lipid peroxidation and the loss of antioxidant enzymes in the heart tissue of ISO treated rats. In addition, GA treatment modulates ISO-induced alterations the expressions of tissue inhibitor of metalloproteinases-1 (TIMP-1), p-AKT, glycogen synthase kinase-3β (p-GSK-3β) and peroxisome proliferators-activated receptor-γ (PPAR-γ) in the heart tissue. Furthermore, molecular analysis (PCR array and western blot) revealed that GA pretreatment prevented inflammation and fibrosis related gene expression pattern in ISO-induced rats. Taken together, the results indicate the cardioprotective effect of GA against ISO-induced inflammation and fibrosis. The antioxidant and anti-inflammatory potential of GA could be considered for its cardioprotective effect in the ISO-treated rats.